AAV-aMTD-Parkin, a therapeutic gene delivery cargo, enhances motor and cognitive functions in Parkinson's and Alzheimer's diseases - Seokwon Lee; Mingu Kang; Seungwoo Lee; Sangsun Yoon; Yeonjin Cho; Dongjae Min; Daye Ann; Jisoo Shin; Young-Ki Paik; Daewoong Jo (Elsevier, 2024)
Neurodegenerative disorders, such as Parkinson's disease (PD) and Alzheimer's disease (AD), have a global prevalence and profoundly impact both motor and cognitive functions. Although adeno-associated virus (AAV)-based gene therapy has shown promise, its application for treating central nervous system (CNS) diseases faces several challenges, including effective delivery of AAV vectors across the blood-brain barrier, determining optimal dosages, and achieving targeted distribution. To address these challenges, we have developed a fusion delivery therapeutic cargo called AAV-aMTD-Parkin, which combines a hydrophobic cell-penetrating peptide sequence with the DNA sequences of AAV and Parkin. By employing this fusion delivery platform at lower dosages compared to zolgensma, we have achieved significant enhancements in cell and tissue permeability, while reducing the occurrence of common pathological protein aggregates. Consequently, motor and cognitive functions were restored in animal models of PD and AD. With its dual functionality in addressing PD and AD, AAV-aMTD-Parkin holds immense potential as a novel class of therapeutic biologics for prevalent CNS diseases.